Analysis of Effect of Dividend Policy, Policies Debt, Profitability and Investment Decision in the Value of The Company - Suhendro, Pinkan Ajeng Maulina, Riana Rachmawati Dewi & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The purpose of this study was to determine the effect of dividend policy, debtpolicy, profitability, and investment decisions in part on the value of thecompany.The data used secondary data, with a population of basic chemicalindustry research company went public listed on the Indonesia Stock Exchange2012-2016 period. The sampling technique is purposive sampling of 65 companiesacquired 12 companies basic chemical industry for five years. Results from thisstudy thatdividend policy (payout ratio) does not affect the value of the company(price to book value) .kebijakan debt (debt to equity ratio) has no effect on thevalue of the company (price to book value). Profitability (return on equity) effecton firm value (price to book value). investment decisions (price earnings ratio)effect on firm value (price to book value) Adjusted R2 of 0.399, which means thatthe value of the company was affected by the dividend policy, debt policy,profitability, and investment decisions. While the remaining 60.1% (0.601) isinfluenced by other factors outside the research.Keywords: dividend policy, debt policy, Profitability, Investment Decision, CompanyValue